2017
DOI: 10.1108/oir-01-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of contextual support on persistent sharing willingness of QQ group members

Abstract: Purpose The purpose of this paper is to explore the ways to encourage members in QQ knowledge-communication groups to persistently share knowledge in terms of contexts and autonomous motivations. Design/methodology/approach Based on self-determination theory, three important contextual factors of QQ knowledge-communication groups were selected as exogenous variables and three typical autonomous motivations as mediating variables to construct a knowledge-sharing model. Internet questionnaire surveys and data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In effect, enterprise social media can affect the social trust when they are used for work and social contact (Kobayashi et al, 2006;Räsänen and Kouvo, 2007;Valenzuela et al, 2009). The use of social media platforms for the same purpose can improve the trust, because a work group can be established on such platforms (Yuan and Liu, 2017). Employees who use these applications gradually build relationship capital and trust among them as communication increases (Sun and Shang, 2014;Cheng et al, 2017).…”
Section: Effect Of Enterprise Social Media Usage On Trustmentioning
confidence: 99%
“…In effect, enterprise social media can affect the social trust when they are used for work and social contact (Kobayashi et al, 2006;Räsänen and Kouvo, 2007;Valenzuela et al, 2009). The use of social media platforms for the same purpose can improve the trust, because a work group can be established on such platforms (Yuan and Liu, 2017). Employees who use these applications gradually build relationship capital and trust among them as communication increases (Sun and Shang, 2014;Cheng et al, 2017).…”
Section: Effect Of Enterprise Social Media Usage On Trustmentioning
confidence: 99%
“…Online brand communities provide opportunities for individuals to browse product-related information, share experiences, and read other consumers' reviews. There are numerous online brand communities with different themes that individuals can join to gain expertise related to a certain brand or keep in touch with different members [4], [5]. Previous research shows that online brand communities have powerful influences on individuals' perceptions and behaviors, such as brand satisfaction [6]- [9]; brand trust, commitment, and engagement [3], [10], [11]; brand loyalty [9], [12], [13]; and repurchase intention [9], [14].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of information technology, individuals are more willing to use virtual communities for communication and information acquisition. In order to solve problems or meet information needs, individuals join in a large number of virtual communities with different themes [2]. Previous research has found that virtual brand communities have important effects on individuals' perceptions and behaviors, such as knowledge sharing [3], brand engagement [4], [5], brand loyalty [6], [7], and repurchase intentions [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The healthy and sustainable development of virtual brand communities is inseparable from community members' continuance participation that can facilitate the integration and cohesion of the virtual community by attracting more people with common interests, needs, or experiences [1], [2], [11]. Members' continuance participation can be divided into active participation and passive participation [1], [12]- [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation